2009
DOI: 10.1679/aohc.72.187
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a three-dimensional and layered (TDL) culture, a novel primary co-culture method for ameloblasts and pulp-derived cells

Abstract: polarity and well-developed intercellular junctions, had PAS positive material in their cytoplasm, and expressed a distinct immunoreactivity for cyotokeratin 14 and amelogenins. Pulpal cells in the gel displayed a strong ALP activity throughout the 3D gel. The current observations have clearly shown that the structural and functional features reminiscent of early secretory ameloblasts could be restored in the enamel organ-derived cells in a TDL culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Using this architecture, the proximity of different cell types can be assayed for morphological changes to cell structure, or migration of cells [23]. In dentistry, the study of early tooth germ cell structure has been observed through the use of 3D and layered cultures that utilise dental tooth pulp and enamel epithelial cells suspended in layers that are then floated in media [68]. This resulted in a cuboidal morphology of enamel epithelial cells, which correlates with developmental effects in vivo.…”
Section: Benefits and Limitations Of Epithelial Cell Coculturementioning
confidence: 99%
See 1 more Smart Citation
“…Using this architecture, the proximity of different cell types can be assayed for morphological changes to cell structure, or migration of cells [23]. In dentistry, the study of early tooth germ cell structure has been observed through the use of 3D and layered cultures that utilise dental tooth pulp and enamel epithelial cells suspended in layers that are then floated in media [68]. This resulted in a cuboidal morphology of enamel epithelial cells, which correlates with developmental effects in vivo.…”
Section: Benefits and Limitations Of Epithelial Cell Coculturementioning
confidence: 99%
“…This resulted in a cuboidal morphology of enamel epithelial cells, which correlates with developmental effects in vivo. Here, the result would have been a simple monolayer if the epithelial cells were studied in monoculture [68]. 3D matrix gels have also demonstrated migration and differentiation when cocultured in layers.…”
Section: Benefits and Limitations Of Epithelial Cell Coculturementioning
confidence: 99%